GAMBARAN KEBIASAAN MAKAN MAKANAN BERESIKO PENYAKIT JANTUNG KORONER PADA ETNIS MINAHASA DI KECAMATAN TOMOHON UTARA KELURAHAN KAKASKASEN 1 - Meilani, Jessica Meilani; Kandou, Grace D.; Ottay, Ronald I.; Kaunang, Wulan P. J. (UNIVERSITAS SAM RATULANGI, 2014)
The coronary heart disease is a disease with the highest death rate yearly in accordance with other diseases in the world.Habitual eating is influenced by cultural factor, tradition, religion and belief. The habitual eating also play a role in theoccurrence process of coronary heart disease. This research was purposed to know the description of the eating habit andits relation with the coronary heart disease risk food of the Minahasa ethnic at North Tomohon Subdistrict Kakaskasen 1Village. The design of research was descriptive study by using survey methods. A hundred and nine were the numbers ofthe patriarchs (KK – Kepala Keluarga) who settled in in Lingkungan 8 of Kakaskasen Village of Tomohon Utara Subdistrict,and the samples were 52 KK. Data was collected using Food Frequency Questionnare (FFQ). The study found 5 Minahasaethnic food which often consumed, namely: Sayur Kangkung Tumis (86,6%), Babi Kecap (65,4%), Sate Babi(65,4%), Brenebon Babi (57,6%), Sup/Kuah Asam Babi (53,8%) and the 5 other types which rare consumed were IkanMas Woku Blanga (100%), Ikan Mas Goreng (100%), Ikan Mas Bakar Rica (100%), RW/Anjing (96,1%), Paniki/Kelelawar(90,4%). No history of the coronary heart disease was obtained on all respondents. On the other hand, this study revealed the history of the coronary heart disease in the family (5,8%), history of hypertension (42,3%), diabetes mellitus (11,5%), dyslipidemia (7,3%), stroke and hyperuricemia (1,9%).Keywords: Habitual Eating, Coronary Heart Disease.